Suggestive potential of political speeches of state leaders - Snytko , Olena (Current issues of Ukrainian linguistics: theory and practice, 2021)
The paper examines the suggestive potential of political speeches of state leaders. The author argues that the greatest political addresses given at turning points in history demonstrate a programming effect and, consequently, are intended as texts with suggestive features. The current study proves that rhythm is the essential feature of a suggestive text. The rhythm is a complex phenomenon built on the balanced alternation or repetition of certain elements (formal and semantic). The distinctive rhythm for political address is established via lexical and, broader, semantic repetition of key verbal elements carrying dominant meanings which comprise two opposite functional textual groups via grammatical (morphological and syntactic) patterns or parallelism, accompanied by phonetic repetition. Such repetition serves the communicative-pragmatic purpose of the suggestor, namely, to consolidate the dominant meanings. The results of this study indicate that emotiogenic attributes (or qualifiers) aimed at emotional "charging" of the target audience are the primary means of suggestion. The texts of political speeches contain the elements of solemn rhetoric and pathetic appeal to the sacred forces. Political addresses of state leaders provide a strong impetus for creating meaningful public narratives favouring one or another political course of society. Furthermore, an informative political speech, which employs suggestive techniques, serves as a potent tool to exercise power over the target audience and as a means to shape public opinion and influence the mood in society. Finally, the political leader plays the role of an authoritative communicator who organizes, structures the individual’s picture of the world, helps to resist communicative warfare and gives people a sense of order in a life of chaos.